2008
DOI: 10.1007/s10557-008-6106-y
|View full text |Cite
|
Sign up to set email alerts
|

Administration of the Rho-Kinase Inhibitor Fasudil Before Ischemia or just After Reperfusion, but not 30 min After Reperfusion, Protects the Stunned Myocardium in Swine

Abstract: We assessed the effect of administration time for fasudil treatment of the stunned myocardium in 40 anesthetized open chest swine. All swine were subjected to 12 min ischemia followed by reperfusion to generate stunned myocardium. Group A (n = 11) received saline in place of fasudil both before ischemia and after reperfusion. Group B (n = 10) received 30 min intravenous fasudil at a rate of 13 µg/kg/min starting 45 min before ischemia and received saline after reperfusion.Groups C (n = 10) and D (n = 9) receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…A deleterious role of RhoA/ROCK signaling in I/R injury has been demonstrated in several in vivo models including mouse, 214 rat, 215217 dog 218 and swine. 219 In these models ROCK inhibition with fasudil 215220 or Y27632 214,215,221 achieved smaller infarct size, less inflammation, attenuated apoptosis, and enhanced cardiac contractile function. The proposed cardioprotective mechanisms of ROCK inhibition include 1) activation of the PI3K/Akt/eNOS signaling pathway 215,216,218,220 and the JAK2/STAT3 signaling pathway; 220 2) reduction of endothelial-leukocyte interaction during ischemia-reperfusion injury by preserving endothelial function 222 and suppression of inflammatory responses; 214216 3) reduction of endothelial cell shape changes and apoptosis through reducing actin cytoskeleton re-organization; 223,224 4) inhibition of myocyte apoptosis through increasing the expression of antiapoptotic Bcl-2 protein, 214 decreasing mitochondria-nuclear translocation of apoptotic-inducing factor through the inhibition of c-Jun NH2-terminal kinase, 217 and reducing endoplasmic reticulum stress through the elevation of sarco-endoplasmic reticulum Ca 2+ -ATPase (SERCA) activity; 220 5) improving energy production through increasing the levels of lactate dehydrogenase and glyceraldehyde-3-phosphate dehydrogenase, normalizing creatine kinase levels, and inhibiting ATP synthase degradation.…”
Section: Rock In Cardiovascular Diseasesmentioning
confidence: 95%
“…A deleterious role of RhoA/ROCK signaling in I/R injury has been demonstrated in several in vivo models including mouse, 214 rat, 215217 dog 218 and swine. 219 In these models ROCK inhibition with fasudil 215220 or Y27632 214,215,221 achieved smaller infarct size, less inflammation, attenuated apoptosis, and enhanced cardiac contractile function. The proposed cardioprotective mechanisms of ROCK inhibition include 1) activation of the PI3K/Akt/eNOS signaling pathway 215,216,218,220 and the JAK2/STAT3 signaling pathway; 220 2) reduction of endothelial-leukocyte interaction during ischemia-reperfusion injury by preserving endothelial function 222 and suppression of inflammatory responses; 214216 3) reduction of endothelial cell shape changes and apoptosis through reducing actin cytoskeleton re-organization; 223,224 4) inhibition of myocyte apoptosis through increasing the expression of antiapoptotic Bcl-2 protein, 214 decreasing mitochondria-nuclear translocation of apoptotic-inducing factor through the inhibition of c-Jun NH2-terminal kinase, 217 and reducing endoplasmic reticulum stress through the elevation of sarco-endoplasmic reticulum Ca 2+ -ATPase (SERCA) activity; 220 5) improving energy production through increasing the levels of lactate dehydrogenase and glyceraldehyde-3-phosphate dehydrogenase, normalizing creatine kinase levels, and inhibiting ATP synthase degradation.…”
Section: Rock In Cardiovascular Diseasesmentioning
confidence: 95%
“…Studies have shown that Rho-kinase (ROCK) is involved in various basic cellular biological activities, and the beneficial effects of ROCK inhibition against I/R injury by fasudil have been well demonstrated [18], [19], [20]. Therefore, in the present study using an in vivo rat heart I/R injury model we aimed to investigate whether ROCK inhibition by fasudil can attenuate the time- related increase in I/R injury through reduced ER stress activation for which PI3K/Akt and JAK2/STAT3 pathways might play differential roles, specifically whether SERCA activity is differentially modulated by these two signaling pathways during the reperfusion period.…”
Section: Introductionmentioning
confidence: 99%
“…Increased RhoA/ROCK activity has been reported in I/R injuries [155,156]. A deleterious role of RhoA/ROCK signaling in I/R injury has been demonstrated in several in vivo models including mouse [155], rat [147,156,157] and swine [158]. In these models ROCK inhibition with fasudil or Y27632 resulted in reduced infarct size, less inflammation, reduced apoptosis and enhanced contractile function.…”
Section: Rock In Cardiovascular Diseases Hypertensionmentioning
confidence: 99%